MURALS AS A VISUAL MEDIA TO DEVELOP A POSITIVE IMAGE OF FOOD SECURITY ACTIVITIES FOR SOCIETY - aisyah, lani siti noor; Purnomo, Hari; Putri, Liza Amalia (Jurnal Ilmiah Publipreneur, 2024)
The context of this research is the phenomenon of a value change of murals in modern society, from a previously negative image to a positive image. Nowadays murals can even become a form of visual media that able to accommodate various sociocultural discourses. The aim of the research is to analyze how murals can be semantically as a contemporar media for various socio-cultural discourses within the visual communication design paradigm. The research uses a case study of a gardening for food security-themed, created by researchers as part of community service activities in Kelurahan Srengseng Sawah, South Jakarta in 2023. Murals as visual culture are analyzed using the design thinking method initiated by John Edward Arnold, then murals are studied as visual culture, and validate to communication psychology theory. The results show that murals has a communication and visual function as an ambient media (to build an atmosphere of activities), aesthetic value, visual text, murals as campaign media that encourages the society to actively participate in gardening activities as part of an independent food security programme led by PKK (Pemberdayaan Kesejahteraan Keluarga) in Kelurahan Srengseng Sawah. By those semantic contents, murals through of a cognitive, affective and behavioral approach, managed to build a positive image and have a positive impact to the community to do gardening activities along with awareness of the importance of independent food safety efforts.